QRIS as a catalyst for growth: Analyzing its role in Tanjung Balai's MSME sector from an Islamic viewpoint - Putri, Dian Ananda; Jannah, Nurul (LPMP Imperium, 2025)
This study examines the role of QRIS (Quick Response Code Indonesian Standard) in enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Balai. It evaluates the Islamic perspective on its use in economic transactions. The research employs a qualitative method with a case study approach. Data was collected through in-depth interviews with MSME actors, traders, and other relevant stakeholders. The findings indicate that QRIS has significantly improved the performance of MSMEs in Tanjung Balai by facilitating transactions, increasing efficiency, and expanding market reach. From an Islamic perspective, the use of QRIS is generally viewed positively, as it aligns with Sharia principles and represents an innovative development in the business sector. However, challenges exist, such as limited digital literacy among MSMEs and uneven infrastructure. Public Interest Statements QRIS has significant potential to improve the quality of MSMEs in Tanjung Balai by providing convenience in transactions, increasing income, and ensuring security in business operations. From an Islamic viewpoint, using QRIS supports Sharia principles and promotes sound business ethics. Therefore, the government and related institutions need to continue supporting the socialization and development of technological infrastructure so that MSME players in the area widely experience the advantages of QRIS